Sociopragmatics of Curse Lexicon Referencing Supernatural Beings in the Sambas Malay Language - Sulissusiawan, Ahadi (Journal Informatic, Education and Management (JIEM), 2025)
This research aims to analyze the use of lexicon of curses based on supernatural beings in the Sambas Malay language from a sociopragmatic perspective. The focus of the research is to understand the social and cultural functions of these curses, both as tools for joking and insulting, and how these curses reflect the cultural values, local beliefs, and identity of the Sambas Malay community. The research method uses a qualitative approach with data collection in the form of oral and written discourse. The analysis was conducted using Dell Hymes' SPEAKING framework to uncover the social context, communicative purpose, and cultural meaning behind the curse words. The research results show that lexicons such as "antu," "setan," dan "tuyul" serve to joke as an effort of familiarity and to strengthen social relationships, as well as to insult to express dominance or dislike. This research contributes to enriching the study of anthropological linguistics by highlighting the role of language in preserving local beliefs and traditions.